The color of Bee Larkham's murder - Harris, Sarah J., 1971- (Touchstone, 2018)
"In the tradition of The Curious Incident of the Dog in the Night-Time, a captivating mystery about a boy with synesthesia--a condition that causes him to see colors when he hears sounds--who tries to uncover what happened to his beautiful neighbor, and if he was ultimately responsible. Thirteen-year-old Jasper Wishart lives in a world of dazzling color that no one else can see, least of all his dad. Words, numbers, days of the week, people's voices--everything has its own unique shade. But recently Jasper has been haunted by a color he doesn't like or understand: the color of murder. Convinced he's done something terrible to his new neighbor, Bee Larkham, Jasper revisits the events of the last few months to paint the story of their relationship from the very beginning. As he struggles to untangle the knot of untrustworthy memories and colors that will lead him to the truth, it seems that there's someone else out there determined to stop him--at any cost. Both a refreshing coming-of-age story and an intriguing mystery, The Color of Bee Larkham's Murder is a poignant and unforgettable read--perfect for fans of bestselling authors such as Fredrik Backman and Graeme Simsion"--